High incidence of TB at a psychiatric hospital - X. Li; X. Pang; C. Mu; F. Zhang; C. Wang; G. Zhang (IJTLD Open)
BACKGROUND: Individuals with mental illness are susceptible to TB. This study aimed to investigate a TB epidemic in a male psychiatric hospital to explore its potential for institutional spread. METHODS: From April 2022 to March 2023, 19 TB cases were diagnosed in a male psychiatric hospital. Epidemiological investigations and screening of close contacts were carried out. RESULTS: A total of 400 psychiatric patients and 160 staff members were screened for TB. The overall positive rate was 37.15%, with 43.09% among patients and 22.93% among staff. Ultimately, a total of 17 psychiatric patients (including 2 index cases, 5 active cases, and 11 confirmed cases) and 2 staff (1 active case and 1 confirmed case) were diagnosed. The overall attack rate was 3.36%, with 4.20% in patients and 1.24% in staff. Whole-genome sequencing revealed that 3 drug-resistant patients from a third Department had mutations at two loci (rpoB and rpsL) with fewer than 6 SNPs. CONCLUSION: Strengthening surveillance and conducting comprehensive epidemiological investigations for any occurrence of two or more TB cases is of utmost importance. Additionally, enhancing diagnostic capabilities and ensuring strict adherence to infection control protocols during patient care are essential measures to prevent TB outbreak.